2011
DOI: 10.3168/jds.2011-4401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mid-infrared spectroscopy for the prediction of detailed protein composition and contents of protein genetic variants of individual milk of Simmental cows

Abstract: Mid-infrared (MIR) spectroscopy was used to predict the detailed protein composition of 1,517 milk samples of Simmental cows. Contents of milk protein fractions and genetic variants were quantified by reversed-phase HPLC. The most accurate predictions were those obtained for total protein, casein (CN), α(S1)-CN, β-lactoglobulin (LG), glycosylated κ-CN, and whey protein content, which exhibited coefficients of determination between predicted and measured values in cross-validation (1-VR) ranging from 0.61 to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 24 publications
11
69
4
2
Order By: Relevance
“…Second, Pacini et al (2008) highlighted a greater frequency of j-CN B allele in BU cattle breed, which is associated with greater casein content (Vallas et al 2012). De Marchi et al (2009), Bonfatti et al (2011) and Niero et al (2016) reported values of casein index that were similar to the one calculated in the present study.…”
Section: Protein Fractionssupporting
confidence: 78%
“…Second, Pacini et al (2008) highlighted a greater frequency of j-CN B allele in BU cattle breed, which is associated with greater casein content (Vallas et al 2012). De Marchi et al (2009), Bonfatti et al (2011) and Niero et al (2016) reported values of casein index that were similar to the one calculated in the present study.…”
Section: Protein Fractionssupporting
confidence: 78%
“…They are just used in laboratory and are not capable of real-time or situ detection. The spectroscopy analysis methods, including the visible (Bogomolov et al 2012), infrared (Rutten et al 2011), midinfrared (Bonfatti et al 2011;Botaro et al 2011), near-infrared (Bogomolov and Melenteva 2013;Feng et al 2013;Kalinin et al 2013), and ultraviolet (Dziuba et al 2001;Rukke et al 2010), have been used to determine protein content in milk widely; however, too complex instruments are needed. Moreover, most of them are difficult to be used in real-time detection.…”
Section: Introductionmentioning
confidence: 99%
“…Equations based on the full spectrum have been developed for the determination of fine milk components such as fatty acid profiles (Soyeurt et al, 2006;Rutten et al, 2009), protein composition (Bonfatti et al, 2011), minerals (Soyeurt et al, 2009), ketone bodies (van Knegsel et al, 2010), citrate (Grelet et al, 2016), and lactoferrin (Soyeurt et al, 2007). Other studies have focused on FT-MIR spectra to build equations predicting technological properties of milk such as milk acidity ), ability to coagulate, firmness of curd, or cheese yield (Dal Zotto et al, 2008;Colinet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%